Venous Thromboembolism: A Comparison of Treatment with Intermittent Constant Dosage Heparin and Continuous Infusion with Laboratory Control - Mant, M.J.; O’Brien, B.; Grace, M.G. (Thrombosis and Haemostasis, 1977)
We are conducting a prospective randomized trial comparing the treatment of venous thromboembolism for 10 days with constant dosage intermittent (I) I.V. heparin 5000 u 4 hrly and with continuous (C) I.V. heparin in comparable dosage with daily dosage adjustment designed to maintain activated partial thromboplastin times between 1½ and 2½ × control values. Patients with massive pulmonary embolism are excluded.Fifty-five patients have now received I heparin and 50 C heparin. Age and sex distributions, clinical diagnoses and factors potentially predisposing to hemorrhage were similar in the 2 groups. The clinical diagnosis was radiologically confirmed in 80 of the 105 patients. Although no patients have had a certain pulmonary embolus during treatment 5 in each group had suggestive clinical and/or radiologic findings. Pain or tenderness occurred at a new site or in an asymptomatic leg in 7 patients on I heparin and in 13 on C heparin. Hemorrhage occurred in 18 patients on I and 16 on C heparin. Major bleeding occurred in 7 patients and was spontaneous in 5 of these, in each group. Minor bleeding occurred in 15 patients on I heparin and 12 on C heparin. Some of these also had major bleeding. No patients have died of bleeding. One patient has died from progressive respiratory failure due to the original emboli. These preliminary results demonstrate that, although mortality is low, both hemorrhage and clinical features suggestive of recurrent thromboembolism are common during the first 10 days of heparin therapy. They also suggest’that continuous administration of heparin with laboratory control may have no significant advantages over the simpler intermittent constant dosage treatment regimen.